2013
DOI: 10.11604/pamj.2013.16.88.2519
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus infection among Sudanese children younger than 5 years of age: a cross sectional hospital-based study

Abstract: IntroductionIn Sudan, rotavirus has been one of the important causative agents of diarrhea among children. Rotavirus A is well known as the leading cause of diarrhea in young children worldwide. It was estimated to account for 41% of hospitalized cases of acute gastroenteritis among children in Sub-Saharan Africa. This study aimed to determine the prevalence and the common clinical presentations of rotavirus A infection among Sudanese children with gastroenteritis seeking management in hospitals.Methods755 Sud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
6
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
6
6
2
1
Order By: Relevance
“…It is similar to data obtained from Iran that 57.8% of rotavirus cases were males [10]. In a study conducted in different hospitals in Sudan, Magzoub et al found that 65.3% of studied children were males [4]. In the present study most of cases (41%) occurred among age group 1-12 months, it is similar to data obtained in Oman that most of rotavirus positive cases were at 7-12 months of age [8].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is similar to data obtained from Iran that 57.8% of rotavirus cases were males [10]. In a study conducted in different hospitals in Sudan, Magzoub et al found that 65.3% of studied children were males [4]. In the present study most of cases (41%) occurred among age group 1-12 months, it is similar to data obtained in Oman that most of rotavirus positive cases were at 7-12 months of age [8].…”
Section: Discussionsupporting
confidence: 87%
“…Magzoub et al (2013) mentioned that about 82% of rotavirus deaths occurred among children in the poorest countries [4]. The disease causes many symptoms mainly diarrhea, nausea, malaise, headache, abdominal cramping, fever and vomiting, however the infection can be symptomless sometimes [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to other studies in Nigeria where rotavirus was detected in slightly higher rates in male than in females (Aminu et al, 2008, Pennap andUmoh 2010;Junaid et al, 2011). Similar studies in other countries such as in South Western Iran (Kajbaf et al, 2013), and in Sudan (Magzoub et al, 2013) have reported higher detection rates of rotavirus infection in males than in females. However, studies from Cameroon (Ndze et al, 2012) reported higher detection rates in females (45.3%) than in males (40.8%).…”
Section: Rotavirus Adenovirussupporting
confidence: 89%
“…The positive rate was higher than that of developed countries, such as England (14.3%) (Sethi et al, 2001); lower than that of some developing countries, such as Thailand (30%) (Chieochansin et al, 2016) and India (23%) (Namjoshi et al, 2014); and similar to the positive rate of rotavirus detection in Sudan (16%) (Magzoub et al, 2013). The danger to males was higher, and the ratio of infected males to females was 1.6:1.…”
Section: Discussionmentioning
confidence: 59%